2017
DOI: 10.1080/21655979.2017.1296613
|View full text |Cite
|
Sign up to set email alerts
|

Molecular strategies to increase the levels of heterologous transcripts inKomagataella phaffiifor protein production

Abstract: Komagataella phaffii (formerly Pichia pastoris) is a well-known fungal system for heterologous protein production in the context of modern biotechnology. To obtain higher protein titers in this system many researchers have sought to optimize gene expression by increasing the levels of transcription of the heterologous gene. This has been typically achieved by manipulating promoter sequences or by generating clones bearing multiple copies of the desired gene. The aim of this work is to describe how these differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…This study also exceeds the recently reported values in a fermenter of 2 L (97.34 U•mL −1 or 97.34 mg•L −1 ) and 30 L (62.64 U•mL −1 or 62.64 mg•L −1 ) of r-TmDEX49A produced in K. phaffii in the optimized fermentation (100 h) methanol-induced manner with a productivity of 0.62 mg•L −1 •h −1 [21]. Despite the wide use of the AOX1 promoter, it has some limitations, as methanol is a highly dangerous compound and even more so when working in large volumes, and storage can also be risky in industry [46,47]. Additionally, being a derivative from petrochemical sources, it may require purification steps to produce food and food additive products [48].…”
Section: High Cell Density Fermentation Of K Phaffii Dex49a-δsp-δn30 ...mentioning
confidence: 99%
“…This study also exceeds the recently reported values in a fermenter of 2 L (97.34 U•mL −1 or 97.34 mg•L −1 ) and 30 L (62.64 U•mL −1 or 62.64 mg•L −1 ) of r-TmDEX49A produced in K. phaffii in the optimized fermentation (100 h) methanol-induced manner with a productivity of 0.62 mg•L −1 •h −1 [21]. Despite the wide use of the AOX1 promoter, it has some limitations, as methanol is a highly dangerous compound and even more so when working in large volumes, and storage can also be risky in industry [46,47]. Additionally, being a derivative from petrochemical sources, it may require purification steps to produce food and food additive products [48].…”
Section: High Cell Density Fermentation Of K Phaffii Dex49a-δsp-δn30 ...mentioning
confidence: 99%
“…This study also exceeds the recently reported values in a fermenter of 2 L (97.34 U.mL -1 or 97.34 mg.L -1 ) and 30 L (62.64 U.mL -1 or 62.64 mg.L -1 ) of r-TmDEX49A produced in K. phaffii in the optimized fermentation (100 h) methanol-induced manner with a productivity of 0.62 mg.L -1 .h -1 [21]. Despite the wide use of the AOX1 promoter, it has some limitations as methanol is a highly dangerous compound and even more so when working in large volumes, and storage can also be risky in industry [45,46]. Also, being a derivative from petrochemical sources, it may require purification steps to produce food and food additive products [47].…”
Section: High Cell Density Fermentation Of K Phaffii Dex49a-δsp-δn30 ...mentioning
confidence: 99%
“…After small-scale pilot experiments, there are multiple ways to improve the efficiency of recombinant protein production in K. phaffii for higher levels of protein yield. For example, it is possible to generate a strain with multiple expression cassettes [ 31 , 32 , 33 ]. This often includes the use of multiple selectable markers or dosage sensitive markers [ 32 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, it is possible to generate a strain with multiple expression cassettes [ 31 , 32 , 33 ]. This often includes the use of multiple selectable markers or dosage sensitive markers [ 32 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%